HUBUNGAN KADAR GLUKOSA DARAH DENGAN FUNGSI KOGNITIF PADA PASIEN STROKE - Muhamad Fathurahman, (2023)
Stroke is a condition that occurs when there is a blockage of blood flow to the brain or a rupture of a blood vessel in the brain. In addition to causing death, stroke can also have an impact on cognitive function. The purpose of this study was to determine the relationship between blood glucose levels and cognitive in stroke patients. A cross-sectional design was employed, involving 30 stroke patients selected through purposive sampling. Cognitive function was assessed using the Montreal Cognitive Assessment Indonesian Version (MoCA-INA), while blood glucose levels were obtained from the patients' medical records. Data were then analyzed using Fisher's exact test. The findings indicated no significant relationship between blood glucose levels and cognitive function in stroke patients (p > 0,05). Consequently, it was concluded that, despite the variability of blood glucose levels among stroke patients, this study did not identify a significant association between blood glucose levels and cognitive function. However, given the limited sample size in this study, further research with a larger sample is necessary to validate the results and gain a more comprehensive understanding of the relationship between blood glucose levels and cognitive function in stroke patients.